Worst-Case Execution Time Analysis of a Real-Time System based on Arduino in CAN Network - Merazga, Ammar; Rahem, Djamel; Moulahcene, Fateh; Kebbal, Djemai; Khelaf, Rostom; Benacer, Imad (Engineering, Technology & Applied Science Research, 2025)
Real-time systems need communication networks, as they often operate across multiple physical nodes. CAN-BUS is a common field bus used in these systems. Such systems require a time-based analysis to meet key deadlines and ensure system safety. This study designs and implements a distributed embedded motor control system using FreeRTOS over CAN-BUS for real-time operation. A prototype was built with low-cost components such as Arduino, L298N, and an MCP2515 module. A WCET analysis was performed on the system. The system has two CAN nodes connected to a PC via PCAN-USB for testing and analyzing using Busmaster software. The first CAN node controls the DC motor speed using a real-time PID controller, and the other manages the motor speed through CAN. The experimental results of the PID controller showed a low steady-state error of less than 0.3%. As the speed increases, there is less overshoot. The settling time ( ) is also short, proving the stability of the system. Πerformance was verified by comparing it with the signals from the Busmaster software. The WCET analysis used the Bound-T tool on the AVR2560 microprocessor (16 MHz without cache or pipeline). The calculated WCETs for three tasks were 1228.88 µs, 210.19 µs, and 2786.25 µs. This work verifies the schedulability of tasks for applications on a FreeRTOS real-time embedded platform. Bound-T is an open-source tool for WCET static analysis that has shown strong potential and can be used to perform precise and reliable temporal analyses.